LONG-WAVE DYNAMICS IN THE CONTEXT OF THE DEVELOPMENT OF INSTITUTIONAL ECONOMIC THEORY - B. A. Yerznkyan (Publishing House of the State University of Management, 2020)
The subject of the study is the long-wave dynamics due to the impact of scientific and technological progress and examined from the standpoint of institutional economics. The goal of the paper is identification of the features of the long-wave dynamics phases from the standpoint of technological, institutional and world-wide structures. Analytical and logical methods of institutional analysis have been used. The need of correcting the long-wave dynamics notions, caused as by objective changes of economic development as well as by the evolving nature of institutional theory has been identified. The results can be used by executive power authorities relating to strategic management of the development and connecting with the design of social and economic institutions that support self-organization and sustainable functioning of ecosystems. It has been proved that the development of economic systems depends on the relevant selection of technological, institutional and world-wide economic structures and ways of managing them. It has been shown that intra-firm transactions are based on the implicit ternary contracts, market with the mediators on the explicit ternary contracts, market without mediators on the explicit binary contracts, and the network transactions in ecosystems are based on the implicit binary contracts.